UXAPP : evaluation of the user experience of digital products through emotion recognition - Erven, Ricardo Cordeiro Galvão Sant’Ana van (2024)
Dissertação (Mestrado Profissional em Computação Aplicada) — Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, Brasília, 2024.